2014
DOI: 10.1007/s10706-014-9823-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Rock Depth Using Simple Kriging, Ordinary Kriging, RVM and MPMR

Abstract: The determination of rock depth is an important task in geotechnical and geological engineering. This article examines the capability of simple kriging, ordinary kriging, Relevance Vector Machine (RVM) and Minimax Probability Machine Regression (MPMR) for prediction of rock depth at any point in Vellore(India). For simple and ordinary kriging, semivariogram model has been developed. RVM is developed based on the Bayesian theory. MPMR is a probabilistic model. Inputs of the models are latitude (L x ) and longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The OK is a geostatistical method that uses the variance function as weights to unbiased optimal estimation. The OK interpolation method uses the variation function to express the spatial variation (Anderson et al, 2006;Viswanathan et al, 2015;Hekmatnejad et al, 2019), according to Eq. 3:…”
Section: Interpolation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OK is a geostatistical method that uses the variance function as weights to unbiased optimal estimation. The OK interpolation method uses the variation function to express the spatial variation (Anderson et al, 2006;Viswanathan et al, 2015;Hekmatnejad et al, 2019), according to Eq. 3:…”
Section: Interpolation Methodsmentioning
confidence: 99%
“…The accuracy of DEM is directly affected by the interpolation algorithm, which makes the application of airborne GNSS in the study of terrain process difficult. Ordinary kriging (OK), radial basis function (RBF), inverse distance weighting (IDW), irregular network triangulated mesh (TIN), and natural neighbor (NN) interpolation algorithms can be used to simulate DEM and address the problems of voids (Bater and Coops, 2009;Erdogan, 2009;Guo et al, 2010;Shen et al, 2012;Chu et al, 2014;Lv et al, 2015;Montealegre et al, 2015;Montealegre et al, 2015;Viswanathan et al, 2015;Chen et al, 2018;Hekmatnejad et al, 2019;Gao et al, 2021). Previous studies have shown that DEM accuracy is significantly affected by factors such as interpolation methods, sampling density, spatial resolution, and terrain changes.…”
Section: Introductionmentioning
confidence: 99%
“…According to Viswanathan et al [62], SK differs from OK in that it employs the global mean of the complete dataset and subsequently incorporates estimated residuals. The equation for UK can be expressed as Equation (5).…”
Section: Skmentioning
confidence: 99%
“…Successful application of this machine learning algorithm can be found in the literature (Jagan et al, 2016b;Kardani et al, 2021a;Kumar et al, 2019;Samui and Kim, 2016;Viswanathan et al, 2015).…”
Section: S R Amentioning
confidence: 99%